2012
DOI: 10.1353/jda.2012.0013
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Of Foreign Direct Investment On Total Factor Productivity And Economic Growth In Turkey

Abstract: The main objective of this paper is to estimate the contributions of Foreign Direct Investment (FDI) to the aggregate growth and whether FDI have had an impact on total factor productivity (TFP) of Turkey for the period 1960-2005 using aggregate production function. This paper argues that the two main channels through which FDI can affect host country economic growth are technology spillovers and physical capital accumulation. Further, it intends to identify the casual linkage among FDI, TFP and economic growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Their results affirmed that it was only the degree of trade openness that determined TFP while other variables showed no significant effect. Meanwhile, Baltabaev (2013) investigated the relationship between FDI and TFP growth in a panel of 49 countries between 1974 and 2008. The author made use of FDI, R&D expenditure, human capital, trade openness, inflation, and population growth as the independent variables.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Their results affirmed that it was only the degree of trade openness that determined TFP while other variables showed no significant effect. Meanwhile, Baltabaev (2013) investigated the relationship between FDI and TFP growth in a panel of 49 countries between 1974 and 2008. The author made use of FDI, R&D expenditure, human capital, trade openness, inflation, and population growth as the independent variables.…”
Section: Related Literaturementioning
confidence: 99%
“…They concluded that lowering macroeconomic instability might have helped in increasing Turkey’s TFP and catch up with EU countries. The impact of FDI on aggregate growth and TFP in Turkey for the period 1960–2005 was examined by Arisoy (2012). Using FDI and physical capital accumulation as the explanatory variables, the results indicated that FDI contributed positively to TFP growth via capital accumulation and technological spillovers.…”
Section: Related Literaturementioning
confidence: 99%
“…It is important to mention that another empirical study by Arısoy (2012) goes through the effects of FDI on total factor productivities and economic growth for Turkey for the period 1960-2005. The empirical results reveal that FDI positively participates in economic growth rate and total factor productivities through technological spillovers and capital accumulations.…”
Section: Empirical Frameworkmentioning
confidence: 99%
“…However, they mostly focus on inward FDI and associated variables. Although a number of studies (Liu and Wang, 2003;Arisoy, 2012;Haskel et al, 2007;Baltabaev, 2014;and Newman et al, 2015) provide evidence for the positive effect of inward FDI on TFP, contradictory results (Fan and Hu, 2007;Murakami, 2007;Irsova and Havranek, 2013;Elmawazini, 2014;and Bitzer and Görg, 2005) were also observed. In a recent study, Herzer and Donaubauer (2017), considering the mixed results, revisited this issue for developing countries for the period 1981-2011.…”
Section: Literature Reviewmentioning
confidence: 99%